Status of Health Management Education in India: Past, Present, and Future - Kalangi, Sunitha; Thakur, Harshad (Frontiers in Public Health, 2019)
This article provides a perspective on the evolution of health management education in India, its current state and the way ahead. Health management originated in India to respond to the administrative needs of a healthcare system and now is moving towards institutional care from its earlier avatar of home healthcare. As the field evolved over time, new roles emerged for health management professionals. Several articles have been published in the past describing the state and growth in the field of health management education system. The article stresses on the need to rationalise the sector and shape its future to suit the needs of over a billion people who use the services of multiple organizations directly or indirectly in a highly dynamic healthcare environment. We have identified the various challenges that affect the sector today; filling vacant positions, matching jobs with training, and changes in curricula required to achieve these matches. Solutions to address these challenges have also been considered, which in our view could be a way forward in this sector.